Assessment of EGFR Mutations in Circulating Tumor Cell Preparations from NSCLC Patients by Next Generation Sequencing: Toward a Real-Time Liquid Biopsy for Treatment - Marchetti, Antonio (Public Library of Science, 2014)
INTRODUCTION: Assessment of EGFR mutation in non-small cell lung cancer (NSCLC) patients is mandatory for optimization of pharmacologic treatment. In this respect, mutation analysis of circulating tumor cells (CTCs) may be desirable since they may provide real-time information on patient's disease status. EXPERIMENTAL DESIGN: Blood samples were collected from 37 patients enrolled in the TRIGGER study, a prospective phase II multi-center trial of erlotinib treatment in advanced NSCLC patients with activating EGFR mutations in tumor tissue. 10 CTC preparations from breast cancer patients without EGFR mutations in their primary tumors and 12 blood samples from healthy subjects were analyzed as negative controls. CTC preparations, obtained by the Veridex CellSearch System, were subjected to ultra-deep next generation sequencing (NGS) on the Roche 454 GS junior platform. RESULTS: CTCs fulfilling all Veridex criteria were present in 41% of the patients examined, ranging in number between 1 and 29. In addition to validated CTCs, potential neoplastic elements were seen in 33 cases. These included cells not fulfilling all Veridex criteria (also known as “suspicious objects”) found in 5 (13%) of 37 cases, and isolated or clustered large naked nuclei with irregular shape observed in 33 (89%) cases. EGFR mutations were identified by NGS in CTC preparations of 31 (84%) patients, corresponding to those present in matching tumor tissue. Twenty-five (96%) of 26 deletions at exon 19 and 6 (55%) of 11 mutations at exon 21 were detectable (P = 0.005). In 4 (13%) cases, multiple EGFR mutations, suggesting CTC heterogeneity, were documented. No mutations were found in control samples. CONCLUSIONS: We report for the first time that the CellSearch System coupled with NGS is a very sensitive and specific diagnostic tool for EGFR mutation analysis in CTC preparations with potential clinical impact.